2022
DOI: 10.1101/2022.09.02.506344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrafast (>400 Hz) network oscillations induced in thalamorecipient cortical layers by optogenetic activation of thalamocortical axons

Abstract: Oscillations of extracellular voltage, reflecting synchronous rhythmic activity in large populations of neurons, are a ubiquitous feature in the mammalian brain and are thought to subserve critical, if not fully understood cognitive functions. Oscillations at different frequency bands are hallmarks of specific brain or behavioral states. At the higher end of the scale, ultrafast (400-600 Hz) oscillations in the somatosensory cortex, in response to peripheral stimulation, were observed in human and a handful of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…Acoustic stimuli evoke not only brainstem but also hippocampal responses within 50 ms post‐stimulation (Brankack & Buzsáki, 1986). Thus, we presume that strong depolarizing input of the acoustic stimulus, impacting the hippocampus in a state prone to generate ripples, can facilitate pyramidal cell‐interneuron interactions producing increased ripple activity (Hu et al, 2023; Stark et al, 2014). The finding that cortical activity in the ripple range (Figure 3) is of lower magnitude than hippocampal ripples indicates that the transient increase in hippocampal ripples occurring shortly after onset of the acoustic stimulation is a direct physiological response to stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic stimuli evoke not only brainstem but also hippocampal responses within 50 ms post‐stimulation (Brankack & Buzsáki, 1986). Thus, we presume that strong depolarizing input of the acoustic stimulus, impacting the hippocampus in a state prone to generate ripples, can facilitate pyramidal cell‐interneuron interactions producing increased ripple activity (Hu et al, 2023; Stark et al, 2014). The finding that cortical activity in the ripple range (Figure 3) is of lower magnitude than hippocampal ripples indicates that the transient increase in hippocampal ripples occurring shortly after onset of the acoustic stimulation is a direct physiological response to stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The principal aim of the current study was to test whether high-frequency oscillations (HFO), interpreted as a measure of population spiking activity (Baker et al, 2003;Curio, 2000;Waterstraat et al, 2021;Hu et al, 2023;Shimazu et al, 2000;Ozaki & Hashimoto, 2011), respond to the physical intensity of the presented stimulus as well as encode fluctuations of the subjectively perceived stimulus intensity. Previous studies, based on local field potentials, extracellular single unit recordings and surface EEG in non-human animals concluded that it is very likely that the intracortical component of HFO originate from the same pyramidal cells as the N20 potential (Shimazu et al, 2000;Ikeda et al, 2005;Baker et al, 2003).…”
Section: Evidence Against the Involvement Of Population Spiking Activ...mentioning
confidence: 99%
“…Following the notion that HFO are generated at basal regions of cortical pyramidal cells (Baker et al, 2003;Curio, 2000;Shimazu et al, 2000;Hu et al, 2023) while the N20 component reflects postsynaptic membrane potentials that propagate back along the apical dendrites towards superficial layers (Wikström et al, 1996;Bruyns-Haylett et al, 2017;Thorpe et al, 2024), the lack of behaviorally relevant HFO fluctuations in the current study in combination with the effects of N20 and alpha band amplitudes in our previous study (Stephani et al, 2021) suggests that moment-to-moment changes of the perceived stimulus intensity are mediated by top-down modulations in apical rather than basal dendritic compartments. This is not only well in line with Dendritic Integration Theory (Bachmann et al, 2020;Aru et al, 2020;Larkum, 2022) but also complies with recent observations of alpha band activity exerting a top-down influence on superficial layers of primary sensory regions (Halgren et al, 2019), as well as with earlier conceptions of the interplay between re-entrant bottom-up and top-down signals in superficial layers at early stages of the somatosensory response cascade (Cauller, 1995;Cauller & Kulics, 1991).…”
Section: Excitability-related Modulation Of Sensory Input May Emerge ...mentioning
confidence: 99%
See 1 more Smart Citation